Alzheimer's disease with cerebrovascular disease: current status in the Asia–Pacific region. (16th March 2016) - Chen, C.; Homma, A.; Mok, V. C. T.; Krishnamoorthy, E.; Alladi, S.; Meguro, K.; Abe, K.; Dominguez, J.; Marasigan, S.; Kandiah, N.; Kim, S.Y.; Lee, D. Y.; et al.
Abstract: Background: There is growing awareness of the coexistence of Alzheimer's disease and cerebrovascular disease (AD+CVD), however, due to lack of well‐defined criteria and treatment guidelines AD+CVD may be underdiagnosed in Asia. Methods: Sixteen dementia specialists from nine Asia Pacific countries completed a survey in September 2014 and met in November 2014 to review the epidemiology, diagnosis and treatment of AD+CVD in Asia. A consensus was reached by discussion, with evidence provided by published studies when available. Results: AD accounts for up to 60% and AD+CVD accounts for 10‐20% of all dementia cases in Asia. The reasons for underdiagnosis of AD+CVD include lack of awareness as a result of a lack of diagnostic criteria, misdiagnosis as vascular dementia or AD, lack of diagnostic facilities, resource constraints and cost of investigations. There is variability in the tools used to diagnose AD+CVD in clinical practice. Diagnosis of AD+CVD should be performed in a stepwise manner of clinical evaluation followed by neuroimaging. Dementia patients should be assessed for cognition, behavioural and psychological symptoms, functional staging and instrumental activities of daily living. Neuroimaging should be performed using computed tomography or magnetic resonance imaging. The treatment goals are to stabilize or slow progression as well as to reduce behavioural and psychological symptoms, improve quality of life and reduce disease burden. First‐line therapy is usually an acetylcholinesterase inhibitor such as donepezil. Conclusion: AD+CVD is likely to be under‐recognised in Asia. Further research is needed to establish the true prevalence of this treatable and potentially preventable disease.